ANALISIS KEBIJAKAN PROGRAM GURU PENGGERAK SEBAGAI UPAYA REGENERASI SUPERVISOR PENDIDIKAN YANG BERKUALITAS DI INDONESIA - Abd. Qadir Muslim; Tamim Mulloh (Journal Publicuho, 2022)
Educational supervision is one of the principal functions and duties of the principal. The principal as a pedagogical supervisor must be guided by the objectives of the pedagogical supervisor, namely to improve teaching and improve the quality of teacher work. In this case, government policies, regulations or programs related to education supervision are needed. Therefore, this study aims to identify government policies and programs in the field of school supervision. The data collection technique used is a literature review with qualitative research methods. This study concludes that government policies and programs in the form of driving teacher programs act as wheels to change education for the better in the future and can reproduce quality supervisors.